Atypical working hours are associated with tobacco, cannabis and alcohol use: longitudinal analyses from the CONSTANCES cohort - Nadine Hamieh; Guillaume Airagnes; Alexis Descatha; Marcel Goldberg; Frédéric Limosin; Yves Roquelaure; Cédric Lemogne; Marie Zins; Joane Matta (BMC, 2022)
Abstract Background This study examined prospective associations between atypical working hours with subsequent tobacco, cannabis and alcohol use as well as sugar and fat consumption. Methods In the French population-based CONSTANCES cohort, 47,288 men and 53,324 women currently employed included between 2012 and 2017 were annually followed for tobacco and cannabis use. Among them, 35,647 men and 39,767 women included between 2012 and 2016 were also followed for alcohol and sugar and fat consumption. Three indicators of atypical working hours were self-reported at baseline: working at night, weekend work and non-fixed working hours. Generalized linear models computed odds of substance use and sugar and fat consumption at follow-up according to atypical working hours at baseline while adjusting for sociodemographic factors, depression and baseline substance use when appropriate. Results Working at night was associated with decreased smoking cessation and increased relapse in women [odds ratios (ORs) of 0.81 and 1.25], increased cannabis use in men [ORs from 1.46 to 1.54] and increased alcohol use [ORs from 1.12 to 1.14] in both men and women. Weekend work was associated with decreased smoking cessation in women [ORs from 0.89 to 0.90] and increased alcohol use in both men and women [ORs from 1.09 to 1.14]. Non-fixed hours were associated with decreased smoking cessation in women and increased relapse in men [ORs of 0.89 and 1.13] and increased alcohol use in both men and women [ORs from 1.12 to 1.19]. Overall, atypical working hours were associated with decreased sugar and fat consumption. Conclusions The potential role of atypical working hours on substance use should be considered by public health policy makers and clinicians in information and prevention strategies.